Cardiac Myxoma with Cerebral Metastases and Chronic Lymphocytic Leukemia/Small Lymphocytic Lymphoma: A Case Report and Review - Maas, Jared A.; Menes, Manuel; Siomin, Vitaly (Journal of Neurological Surgery Reports, 2020)
Background Cardiac myxomas, the most common primary cardiac tumors, are generally benign neoplasms. Primary cardiac lymphoma is a rare cardiac malignancy with a very poor prognosis. Here we present a case of a cardiac myxoma with cerebral metastases and chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) arising within the cerebral metastases.Case description A 62-year-old man, who presented with symptoms of multiple transient ischemic attacks, was found to have a left atrial myxoma. Twelve months after excision of the myxoma, the patient experienced a recurrence of neurologic symptoms. Brain magnetic resonance imaging revealed multiple hemorrhagic masses. Craniotomy was performed to resect the lesions. Histopathologic examination confirmed cardiac myxoma metastases and a small lymphocytic infiltrate within the tumor consistent with CLL/SLL.Conclusion Including the present case, there are 27 cases of cardiac myxoma cerebral metastases and 22 cases of lymphomas arising within myxomas. The present case is the first known instance of both entities in the same patient. There is no standard management for either cardiac myxoma metastases or lymphoma within a myxoma. For both diseases, surgical excision is the primary treatment modality, but postoperative chemotherapy and/or radiation have been attempted. Myxomas may create a chronic inflammatory state that could lead to the development of CLL/SLL.
Keywords: cardiac myxoma; atrial myxoma; cerebral metastases; lymphoma; CLL/SLL